Experiences of Adults Following an Autism Diagnosis - Hens, Kristien (Springer International Publishing, 2018)
'This is possibly the best book on autism research this year. It is a very rich book, which is worthwhile for those who are prepared to leave the path of the instrumental and choose deeper reflection. It is a pioneer in the field of free and equal cooperation between academia and lived experience. There are not many books where the authors are sincere in their questioning without wanting to push through their own agenda.' -Translated review of the original Dutch publication on tistje.com, Autism Experience Blog Since 2008 (December 2017). This book explores adult experiences of autism diagnosis. Focusing on the experiences of 21 interviewees, the structure of the book mirrors the seven stages undergone upon diagnosis, and raises important questions about modern society and the self, amidst this life-changing news. Analysing a broad range of empirical interview data including adults who had experiences of other diagnoses, and adults who seemed to function normally before their autism diagnosis, the authors use these stories to examine how autism diagnosis can be extremely important and helpful, but also generate a great deal of negativity. Illuminating a range of testimonies that have previously been kept in the shadows, this book will not only appeal to students and scholars of autism in adults, but also to practitioners as well as adults who have been diagnosed with autism. Kristien Hens is Lecturer in Ethics at the University of Antwerp, Belgium, and also holds a research position at KU Leuven, Belgium. Her research interests centre around the ethics of psychiatric diagnosis, the models of biology in ethics, and ethics of genetics. Raymond Langenberg is a trainer and management consultant for Diversity BVBA, of which he is also a co-owner. He is also a researcher for the independent think-tank Campus Gelbergen, where his research focuses on experiencing, surviving and living with diagnostic processes.